Missio Dei in the Context of Self-Proclaimed Spiritual Leaders in South Africa: A Missiological Perspective - Kgatle, Mookgo Solomon (The international journal of religion and spirituality in society, 2022)
Missio Dei achieves its goal of total redemption by embracing other sub-missions such as Missio Christos, Missio Spiritus, and Missio Ecclesiae. The argument here is that some self-proclaimed spiritual leaders in South Africa continue to undermine and contradict the goal of Missio Dei through their controversial practices. Various scholars have made some important scientific attempts to uncover the effects of such conduct on the Christian religion. However, very little or no work has been done to assess such conduct in the context of Missio Dei. Using a literature review, this article assesses the negative impact of the conduct of self-proclaimed spiritual leaders on Christian efforts to achieve the goal of Missio Dei. This is important for a broader understanding of the Christian mission in societies, particularly regarding the role of South African churches in finding a better life for all in line with the purpose of Missio Dei.